Aspek Tindakan dan Perilaku dalam Kemiskinan: Studi pada Masyarakat Nelayan Kabupaten Pesisir Selatan Sumatera Barat - ., Syahrizal; Meiyenti, Sri; Ekaputra, Rinaldi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2011)
There is a unique stratification within the fishermen society; highest position is held by the owner of the ship, middle position is tungganai (guardian), and the lowest is the crew (labor fishermen) and traditional fishermen. Poverty is in the lowest end. They struggle difficultly to go out of their poverty. In terms of motivation, the poor fishermen work hard to have a better life. However, the condition and situation do not give them the chance to escape poverty. Key words: poverty, fishermen